Handgrip strength and its association with functional independence, depressive symptoms and quality of life in older adults. (December 2017) - Gopinath, Bamini; Kifley, Annette; Liew, Gerald; Mitchell, Paul
Highlights: Handgrip strength is a proxy for muscle strength. A greater decline in handgrip strength was observed with increasing age in men than in women. Handgrip strength was inversely associated with impaired activities of daily living. Greater handgrip strength was linked to reduced reliance on support services. Abstract: We assessed the associations between handgrip strength and functional independence, quality of life and depressive symptoms in 947 participants aged 65 years or over. Handgrip strength was measured with a dynamometer. Use of formal support and family/friend support was self-reported. Activities of daily living (ADL), quality of life and depressive symptoms were assessed using validated scales. Mean handgrip strength was 27.1 kg (±10.3). Each 10 kg increase in handgrip strength was associated with 39% reduced odds of impaired instrumental ADL. Handgrip strength was inversely associated with use of both formal and family/friend support. Handgrip strength was independently associated with functional independence.